2014
DOI: 10.1098/rspb.2013.2842
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up regulation of a pole-ward migratory predator population

Abstract: As the effects of regional climate change are most pronounced at polar latitudes, we might expect polar-ward migratory populations to respond as habitat suitability changes. The southern elephant seal (Mirounga leonina L.) is a pole-ward migratory species whose populations have mostly stabilized or increased in the past decade, the one exception being the Macquarie Island population which has decreased continuously over the past 50 years. To explore probable causes of this anomalous trend, we counted breeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 68 publications
(144 reference statements)
3
39
1
Order By: Relevance
“…A growing body of evidence, including this study, links changes in sea ice distribution and dynamics with the decrease in seal numbers at Macquarie Island Van den Hoff et al, 2014). This decrease stands in contrast to all other southern elephant seal populations that are either stable or increasing .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A growing body of evidence, including this study, links changes in sea ice distribution and dynamics with the decrease in seal numbers at Macquarie Island Van den Hoff et al, 2014). This decrease stands in contrast to all other southern elephant seal populations that are either stable or increasing .…”
Section: Discussionmentioning
confidence: 66%
“…Southern elephant seal populations occur in four genetically distinct stocks (Corrigan, Fabiani, & Chauke, 2016;Slade, Moritz, Hoelzel, & Burton, 1998). The proximate mechanism of how food availability affects population growth is still unclear but recruitment into the population is lower when sea ice duration is greatest (Van den Hoff et al, 2014). However, the Macquarie Island population (which contains more than 90% of the overall Macquarie stock in the southern Pacific) is decreasing, and has been doing so for several decades Van den Hoff et al, 2014).…”
Section: Our Knowledge Of the Basic Biology And Distribution Of Southernmentioning
confidence: 99%
“…While the major populations at Iles Kerguelen and Heard Island, Peninsula Valdes and South Georgia have stabilized or increased [9], the Macquarie Island population in the southern Pacific Ocean has declined continuously at a mean rate of 0.8% per annum since the 1950s [10]. Although the cause of this decline remains unknown, it is thought to be due to changing oceanic conditions leading to reductions in the foraging success of Macquarie Island breeding females through alterations in the availability or quality of their prey.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long-term decline in the Macquarie Island population [22], our study shows that a mechanism for safely reducing the age of primiparity does not seem to exist. Instead, we found that the cost of first reproduction at age three remained very high.…”
Section: Discussionmentioning
confidence: 94%